A comparison of melt depletion, thermal structure and metasomatism of proterozoic mantle lithosphere in the Namaqua-Natal and Rehoboth Provinces of Southern Africa - Shiimi, Ellwin Taleni (Department of Geological Sciences, 2017)
Major and trace element mineral data are presented for garnet and spinel bearing peridotite xenolith suites from four Late Cretaceous kimberlites to the west of the Kaapvaal craton in two Proterozoic terranes: Hoedkop and Pofadder in the north-western Namaqua-Natal Province and Rietfontein and Louwrensia (Gibeon) in the Rehoboth Province. These are used to constrain and compare the thermal structure, the extents of melt extraction and metasomatism of the two mantle terranes with each other and with the Archaean Kaapvaal craton. Xenoliths from the Rietfontein and Pofadder localities have never previously been studied in detail. The information from this study is crucial for understanding the thermal and chemical evolution of Southern Africa's off-craton lithospheric mantle and the various processes (e.g., kimberlite and other magmatism, continental breakup) that have affected it. Mineral thermobarometry from a variety of independent thermobarometers indicates that, at pressures less than about 4 GPa, xenoliths from the Rehoboth Province (Louwrensia and Rietfontein) lie on or very near the Kaapvaal geotherm and between the 40mWm⁻² and 45mWm⁻² conductive geotherms, demonstrating that the lithospheric mantle in the Rehoboth Province was thermally similar to that of the Kaapvaal craton during the Late Cretaceous. In contrast, peridotites from the Namaqua-Natal Province (Hoedkop and Pofadder) in this pressure range fall at temperatures approximately 100°C - 200°C warmer than the Kaapvaal geotherm at any given depth and lie between the 45mWm⁻² and 50 mWm⁻² conduction geotherms, suggesting a Phanerozoic thermal disturbance in these regions. At higher pressures, samples from both terranes (represented only by Louwrensia and Hoedkop) fall above the Kaapvaal geotherm. However, these deeper, higher temperature peridotites are mostly sheared and indicate localised melt-rock interaction, therefore are not likely representative of the general thermal state of the lithosphere. Peridotites from the four suites have similar mineral major element compositions and their compositional variations fall well within the range of other southern Africa off-craton xenolith localities. Most garnets have smooth REE patterns with LREE depletions and relatively enriched, flat MREE - HREE abundances and patterns, while most clinopyroxenes have negatively sloping REE patterns with maximum enrichments in Nd and Sm. The average extents of melting beneath both Proterozoic provinces are moderate, and the samples are more fertile, on average, than cratonic lithospheric mantle. Peridotites from Louwrensia (Gibeon) appear to have experienced the greatest extents of melt extraction, as garnets from this locality extend to the lowest Y contents and some display strongly sinusoidal REE patterns similar to cratonic subcalcic garnets, suggesting that all of the REE were initially strongly depleted prior to metasomatism. A notable difference between the two terranes is that peridotites from Gibeon and Rietfontein (Rehoboth Province) show well developed trace element equilibrium between clinopyroxene and garnet, whereas those from Hoedkop and Pofadder (NW Namaqua-Natal Province) display significant disequilibrium. Although all peridotites show evidence for metasomatic incompatible element enrichments, some peridotites from Hoedkop show strong disequilibrium in Rb, Ba, Th and Nb (with clinopyroxene being overly enriched in these elements) and all Pofadder peridotites show major disequilibrium, with clinopyroxene being overly enriched in Ba and Nb and overly depleted in the middle and heavy REE relative to garnet. Further, clinopyroxenes from Pofadder peridotites are unique in that they have linear REE patterns, with maximum enrichment in La, in contrast to clinopyroxenes from all other localities in this study, which show concave-down patterns in the light to middle REE. Differences in the likely nature of the metasomatising agents affecting the lithosphere of the two off-craton terranes are discussed, as well as implications for the region's geological evolution.